Congenital Toxoplasmosis: The State of the Art - Bollani, Lina; Auriti, Cinzia; Achille, Cristian; Garofoli, Francesca; De Rose, Domenico Umberto; Meroni, Valeria; Salvatori, Guglielmo; Tzialla, Chryssoula (Frontiers in Pediatrics, 2022)
Infection with the protozoan parasite Toxoplasma gondii occurs worldwide. Usually causes no symptoms. However, a primary infection of pregnant women, may infect the fetus by transplacental transmission. The risk of mother-to-child transmission depends on week of pregnancy at the time of maternal infection: it is low in the first trimester, may reach 90% in the last days of pregnancy. Inversely, however, fetal disease is more severe when infection occurs early in pregnancy than later. Systematic serologic testing in pregnant women who have no antibodies at the beginning of pregnancy, can accurately reveal active maternal infection. Therefore the risk of fetal infection should be assessed and preventive treatment with spiramycin must be introduced as soon as possible to reduce the risk of mother-to-child transmission, and the severity of fetal infection. When maternal infection is confirmed, prenatal diagnosis with Polymerase Chain Reaction on amniotic fluid is recommended. If fetal infection is certain, the maternal treatment is changed to a combination of pyrimethamine-sulfonamide and acid folinic. Congenitally infected newborns are usually asymptomatic at birth, but at risk for tardive sequelae¸ such as blindness. When congenital infection is evident, disease include retinochoroiditis, cerebral calcifications, hydrocephalus, neurocognitive impairment. The diagnosis of congenital infection must be confirmed at birth. In congenital toxoplasmosis management, specific therapy and follow-up with multidisciplinary counseling, must be guaranteed.